2021
DOI: 10.1161/strokeaha.120.031903
|View full text |Cite
|
Sign up to set email alerts
|

Choline Pathway Nutrients and Metabolites and Cognitive Impairment After Acute Ischemic Stroke

Abstract: Background and Purpose: Choline metabolism was suggested to play pathophysiological roles in nervous system and atherosclerosis development. However, little is known about the impacts of choline pathway nutrients and metabolites on poststroke cognitive impairment. We aimed to prospectively investigate the relationships between circulating choline, betaine, and trimethylamine N-oxide with cognitive impairment among acute ischemic stroke patients. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…Many reports have shown that supplementing the maternal (during gestation and lactation) diet with additional choline benefits cognition [34][35][36]. A recent study showed that Chinese ischemic stroke patients with higher choline and betaine levels had a lower risk of cognitive impairment, using data derived from CATIS (China Antihypertensive Trial in Acute Ischemic Stroke) [37]. The effectiveness of choline intake was allied with the findings of our study.…”
Section: Discussionsupporting
confidence: 80%
“…Many reports have shown that supplementing the maternal (during gestation and lactation) diet with additional choline benefits cognition [34][35][36]. A recent study showed that Chinese ischemic stroke patients with higher choline and betaine levels had a lower risk of cognitive impairment, using data derived from CATIS (China Antihypertensive Trial in Acute Ischemic Stroke) [37]. The effectiveness of choline intake was allied with the findings of our study.…”
Section: Discussionsupporting
confidence: 80%
“…Experimental studies suggested that dietary supplementation with choline could increase the neuroprotective cellular response, facilitate development of collateral circulation, and improve ischemic stroke outcomes in a rat model [8][9][10]. Our recent prospective study found that patients with higher plasma choline and betaine levels had a lower risk of cognitive impairment after ischemic stroke [24].…”
Section: Discussionmentioning
confidence: 79%
“…Experimental studies suggested that dietary supplementation with choline could increase the neuroprotective cellular response, facilitate development of collateral circulation, and improve ischemic stroke outcomes in a rat model [8–10]. Our recent prospective study found that patients with higher plasma choline and betaine levels had a lower risk of cognitive impairment after ischemic stroke [24]. PSD is another frequent neuropsychiatric complication following ischemic stroke; however, very limited population‐based studies have investigated the relationships between circulating choline pathway nutrients and PSD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that choline metabolism plays pathophysiological roles in central nervous system (CNS) diseases. For instance, choline metabolism has a potentially prognostic role in cognitive impairment after stoke ( 58 ). Choline is the precursor of neurotransmitter acetylcholine and also acts as an agonist for the receptors that could regulate CNS immune responses, and their dysregulation is associated with the pathogenesis of several neurological diseases ( 59 ).…”
Section: Discussionmentioning
confidence: 99%